2009
DOI: 10.1177/1080569909336951
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Preparing Students for Mock Interviews

Abstract: STUDIES HAVE SHOWN the importance of employment interview preparation in boosting the confidence and performance of students and jobseekers when they interview. This article reviews several techniques for preparing students for mock job interviews and, hence, actual job interviews.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Criteria for appropriate answers and appropriate questions were derived from the interview skills literature (e.g., Frequently Asked Questions About Graduate School, ..; Greenwood, ; Hansen, Oliphant, Oliphant, & Hansen, ; Hollandsworth, Kazelskis, Stevens, & Dressel, ) and refined through feedback from the director of a career center at a university (see Supporting Information for specific questions and answers). Given one of the seven types of interview questions, an appropriate answer was scored as correct if the answer met all criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Criteria for appropriate answers and appropriate questions were derived from the interview skills literature (e.g., Frequently Asked Questions About Graduate School, ..; Greenwood, ; Hansen, Oliphant, Oliphant, & Hansen, ; Hollandsworth, Kazelskis, Stevens, & Dressel, ) and refined through feedback from the director of a career center at a university (see Supporting Information for specific questions and answers). Given one of the seven types of interview questions, an appropriate answer was scored as correct if the answer met all criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Many software programs are now available for such electronic mock interviews, and both electronic mock interviews and face-to-face mock interviews have been shown to increase student confidence and success at interviews (Baur et al, 2013;Hansen, Oliphant, Oliphant, & Hansen, 2009). …”
Section: Mock Employment Interviewmentioning
confidence: 99%
“…Evidence supporting the value of practice or 'mock' interviews towards gaining employment has been reported in many fields. A study reviewing the best practices for preparing business students ahead of job interviews demonstrated that interview practice boosts students confidence and strengthens their interview performance (11). This correlates with many other sources who have equally provided commentary towards the benefits of practice interviews and their value towards successful interview outcomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 66%